Modular Oxidation of Cytosine Modifications and Their Application in Direct and Quantitative Sequencing of 5‑Hydroxymethylcytosine - Xu, Haiqi; Chen, Jinfeng; Cheng, Jingfei; Kong, Linzhen; Chen, Xiufei; Inoue, Masato; Liu, Yibin; Kriaucionis, Skirmantas; Zhao, Meiping; Song, Chun-Xiao (Journal of the American Chemical Society, 2023)
Selective, efficient, and controllable oxidation of cytosine modifications is valuable for epigenetic analyses, yet only limited progress has been made. Here, we present two modular chemical oxidation reactions: conversion of 5-hydroxymethylcytosine (5hmC) into 5-formylcytosine (5fC) using 4-acetamido-2,2,6,6-tetramethylpiperidine-1-oxoammonium tetrafluoroborate (ACT+BF4 –) and further transformation of 5fC into 5-carboxycytosine (5caC) through Pinnick oxidation. Both reactions are mild and efficient on double-stranded DNA. We integrated these two oxidations with borane reduction to develop chemical-assisted pyridine borane sequencing plus (CAPS+), for direct and quantitative mapping of 5hmC. Compared with CAPS, CAPS+ improved the conversion rate and false-positive rate. We applied CAPS+ to mouse embryonic stem cells, human normal brain, and glioblastoma DNA samples and demonstrated its superior sensitivity in analyzing the hydroxymethylome.